2009
DOI: 10.1590/s1020-49892009000900005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of retinopathy of prematurity: an institutional cross-sectional study of preterm infants in Brazil

Abstract: Overall incidence of ROP in this institutional study (25.5%) was comparable to international results from developed countries. A comprehensive countrywide survey on ROP in Brazil is recommended to determine any regional differences in disease prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…Many ROP studies screened only infants born with less than 32 weeks’ gestation or with less than 1500 g of BW [ 4 , 11 ]. In our study, however, we went further and also included infants with more than 1500 g or more than 32 weeks’ gestation with determined risk factors associated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many ROP studies screened only infants born with less than 32 weeks’ gestation or with less than 1500 g of BW [ 4 , 11 ]. In our study, however, we went further and also included infants with more than 1500 g or more than 32 weeks’ gestation with determined risk factors associated.…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of ROP at any stage and of type 1 prethreshold ROP in this subgroup were at intermediate levels of the range reported in Brazilian studies that used the same selection criteria. Fortes Filho et al [ 4 ] found an incidence of ROP at any stage and of type 1 prethreshold ROP of 29.6 and 7% respectively. Conversely, Gonçalves et al [ 11 ] found an incidence of ROP at any stage and of type 1 prethreshold ROP of 44.5 and 1.8% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neovascularization in the retina due to ROP is similar to retinopathies, such as diabetic retinopathy 45. The incidence of ROP varies considerably from country to country depending on the economy, social conditions, and the quality of the infant health care system 6–8. Previous studies have reported an increase in the incidence of blindness, visual loss, and impairment due to ROP 9.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, a incidência de retinopatia apresenta uma ampla variação entre os diversos serviços, situando-se em torno de 25 a 29% em Porto Alegre 19 e São Paulo 20,21 , e chegando até a taxa de 63% em um serviço de neonatologia na cidade de Natal (RN) 22 , considerando-se RNs com peso de nascimento menor de 1500 gramas.…”
Section: Introductionunclassified